Constructing irreducible polynomials with prescribed level curves over finite fields - Mihai Caragiu (International Journal of Mathematics and Mathematical Sciences)
We use Eisenstein's irreducibility criterion to prove that there exists an absolutely irreducible polynomial P(X,Y)∈GF(q)[X,Y] with coefficients in the finite field GF(q) with q elements, with prescribed level curves Xc:={(x,y)∈GF(q)2|P(x,y)=c}.